Test–retest reliability of touchscreen DriveSafe DriveAware. (27th December 2020) - Johnston, Belinda J.; O'Donnell, Joan M.; Manuguerra, Maurizio; Davidson, Andrew S.
Abstract: Introduction: This prospective study examines the test–retest reliability of touchscreen DriveSafe DriveAware (DSDA). In a future study, the authors intend assessing the usefulness of DSDA to measure progress of patients undergoing treatment for neurological conditions. Evidence of test–retest reliability is required first. Methods: Australian adults with current driver's licences ( N  = 39) aged 20 to 91 years ( M age  = 58) recruited from a convenience sample were assessed with DSDA. The assessment was repeated 6 weeks, 6 months, and 12 months later to match planned assessments of patients undergoing neurosurgical treatment in future research. DSDA classification, DriveSafe subtest score, and DriveAware subtest scores were analysed as a whole sample, and in three age groups. Results: DSDA classification and DriveAware scores were consistent over repeated tests. DriveSafe scores increased between test 1 and 2 ( p  = .006), and thereafter no significant change from test 2 to 4. DriveSafe scores of older participants (70+ years) increased between test 1 and 2 more notably than younger participants' scores. No DriveSafe scores decreased over time. Conclusion: DSDA classification and DriveAware scores demonstrated test–retest reliability for all age groups. DriveSafe scores did not demonstrate test–retest reliability between test 1 and 2 for participants 70+ years. However, DriveSafe scores demonstrated test–retest reliability after test 2, possibly indicating an initial learning effect for the DriveSafe score only. The authors posit that this result may have been influenced by older adults' reduced familiarity with iPad technology at first assessment. Further longitudinal research is required to confirm whether these results are consistent in a sample population with diagnosed cognitive impairment. Future research will assess whether repeated assessment of DSDA may be useful for monitoring and screening cognitive fitness to drive in patients who have undergone neurosurgical treatment and whether declining scores may indicate cognitive changes in ability to drive.